Interlocking Directorates: A Strategy for Reducing Environmental Uncertainty - Schoorman, F. David; Bazerman, Max H.; Atkin, Robert S. (Academy of Management Review, 1981)
F. David Schoorman, Max H. Bazerman, Robert S. Atkin, Interlocking Directorates: A Strategy for Reducing Environmental Uncertainty, The Academy of Management Review, Vol. 6, No. 2 (Apr., 1981), pp. 243-251